A corrected benzene nitration three-step mechanism derived by DFT calculation and MO theory - Shi, Hongchang (European Journal of Chemistry, 2023)
Density-functional theory (DFT) calculations at the LC-wHPBE/6-311++G(d,p) level found that the textbook three-step nitration mechanism of benzene in mixed acids was seriously wrong. Step 1 of generating nitronium ion (NO2+) is not spontaneous, the NO2+ is generated by Lewis collision, and needs to overcome a barrier Ea = 18 or 22 kcal/mol in mixed acid or in nitric acid. Obtaining the Ea of the Lewis collision by quantum chemical calculations is a highlight of the study. The reaction system (NO2+ + H2O) + HSO4⎺ or + NO3⎺ or + nH2O (n ≥ 1) can make NO2+ spontaneously change to HNO3 through a poly(≥3)-molecular acidification. Sulfuric acid can greatly reduce [H2O] and increase [NO2+]. Therefore, the nitration rate in mixed acid is much faster than that in nitric acid. Step 2, C6H6 + NO2+, is an electrophilic addition, follows the transition state theory, and needs to overcome a low barrier, ΔE* = 7 kcal/mol. The product of Step 2 is the σ-complex C6H6-NO2+. The essence of the electrophilic addition is the transfer of HOMO-1 electrons of C6H6 to LUMO of NO2+. Step 3 is a spontaneous Lewis acid-base neutralization without any barrier, and generates the target product nitrobenzene C6H5NO2. NO2+ and σ-complex are the two active intermediates in nitration. The benzene nitration rate control step is not Step 2 of generating σ-complex, but is Step 1 to generate NO2+. The DFT calculation obtains the barriers Ea and ΔE*, the reaction heats ΔHσ and ΔHp of each step of the nitration, resulting in the total nitration reaction heat ΔH = -35 kcal/mol. It is consistent with the experimental ΔH = -34 kcal/mol. Based on the results, a corrected benzene nitration three-step mechanism proposed.